2007
DOI: 10.1094/pdis-91-4-0463a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Leaf Spot Caused by Cladosporium herbarum on Centaurea solstitialis in Greece

Abstract: Centaurea solstitialis L. (yellow starthistle), family Asteraceae, an invasive weed in California and the western United States, is targeted for biological control. In the summer of 2003, an epidemic of unknown etiology on dying C. solstitialis plants was observed near Kozani, Greece (40°22′07″N, 21°52′35″E, elevation, 634 m). Plants had necrotic light brown leaf spots on the lower leaves and the decurrent leaf bases along the stems. Often, necrotic lesions extended along the stems to the capitula. Virtually a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Twenty-six strains of four species of Cladosporium , collected from diseased leaves and pods of Vicia faba , were tested for their pathogenicity effect on Vicia faba seedlings as method described with Berner et al 26 . Vicia faba seeds were grown in a glasshouse.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-six strains of four species of Cladosporium , collected from diseased leaves and pods of Vicia faba , were tested for their pathogenicity effect on Vicia faba seedlings as method described with Berner et al 26 . Vicia faba seeds were grown in a glasshouse.…”
Section: Methodsmentioning
confidence: 99%
“…The re-inoculation test of pathogenicity was done by the method according to Berner et al (2007), the pathogen was injected on PDA media and incubated at 28 ℃ for 11 days. The harvested conidia were suspended in sterilized water at 1 x 10P 6 P Conidia/ ml, the sweet melon fruits were sprayed by the conidial suspension then covered with bags and incubated at 28℃ for two weeks.…”
Section: Pathogenicity Testmentioning
confidence: 99%
“…Perelló et al (2003) reported the infection of wheat leaves by m Disease symptoms on the leaves of H. muticus inoculated with a conidial suspension prepared from a single-spore isolate of C. herbarum from a diseased H. muticus plant C. herbarum in Argentina. The fungus also causes leaf spot disease of Centaurea solstitialis in Greece (Berner et al 2007) and Caltha leptosepala (marsh marigold) in North America (Johnson et al 2008). In Egypt, C. herbarum causes leaf spot disease in Cleome amblyocarpa, Haplophyllum tuberculatum, and Pluchea dioscorides, which grow naturally in the Mediterranean coastal area (El Naggar and Abdel-Hafez 2003).…”
Section: Isolation and Identification Of The Pathogenmentioning
confidence: 99%
“…Pathogenicity was tested by the inoculation method described by Berner et al (2007). The isolate was grown on PDA.…”
Section: Pathogenicitymentioning
confidence: 99%